To evaluate the expression \( 3 \cdot 2 - 1(-10) - 3 + 12 \), we can follow the order of operations:
-
Perform the multiplication: \[ 3 \cdot 2 = 6 \] Now substitute this back into the expression: \[ 6 - 1(-10) - 3 + 12 \]
-
Next, handle the multiplication \( -1(-10) \): \[ -1(-10) = 10 \] Now the expression is: \[ 6 + 10 - 3 + 12 \]
-
Proceed with addition and subtraction from left to right: \[ 6 + 10 = 16 \] Then: \[ 16 - 3 = 13 \] Finally: \[ 13 + 12 = 25 \]
Therefore, the result of the evaluation is \( 25 \).
However, 25 is not among the provided options. It seems there may have been a misinterpretation in the expression or a calculation error in the listed options.
Let's recap the calculation step by step:
- From our working out: \[ 3 \cdot 2 = 6 \] \[ -1(-10) = 10 \] Therefore combining: \[ 6 + 10 - 3 + 12 = 25 \]
So, upon evaluating step by step, the final confirmed answer is indeed \( 25 \). However, since this isn't an option, there might be a reevaluation needed on either the provided options or the expression itself.